Instrument performance management in vocational music education: Relationship between self-efficacy perception and learning approaches - Ajda Aylin Can (Journal of Pedagogical Research)
Students receiving instrument education in institutions providing vocational music education are expected to enhance their self-efficacy perceptions regarding their instruments, identify their motivations, and develop strategies for their learning approaches. These efforts aim to address deficiencies encountered during the educational process and foster personal improvement. This study aimed to examine the relationship between the instrument performance management self-efficacy perceptions of vocational music education students and their learning approaches to instruments. Additionally, the study investigated whether students’ learning approaches and self-efficacy perceptions varied based on factors such as gender, age, voluntary selection of their instrument, and engagement in other employment. The study sample comprised students from two universities in the Marmara region of Türkiye offering vocational music education. Data were collected using a relational survey method and included the personal information form developed by the researcher, the Approaches to Instrument Learning Scale, and the Instrument Performance Management Self-Efficacy Perception Scale. The findings revealed a generally positive relationship between students' instrument performance management self-efficacy perceptions and their learning approaches to instruments. Furthermore, it was found that students’ learning approaches significantly predicted their self-efficacy perceptions. The study also determined that learning approaches varied based on gender, academic grade, and voluntary selection of instruments. Additionally, self-efficacy perceptions differed in some sub-dimensions depending on whether students voluntarily chose their instruments and whether they were employed in another field.